Assessing the impact of a business-oriented educational course on the development of entrepreneurial thinking in pre-service primary school teacher - Nurzhaugan Balginbayeva; Aktoty Akzholova; Zhuldyzai Baimaganbetova; Abay Duisenbayev; Saule Yerkebayeva; Alua Smanova; Elmira Aitenova (Institute of Advanced Engineering and Science, 2026)
This study aimed to assess the impact of a business-oriented educational course on the development of key components of entrepreneurial thinking among pre-service primary school teachers. The research involved 220 students from M. Dulati Taraz University. A pre-test/post-test design was used with an author-developed questionnaire. Entrepreneurial thinking was assessed both before and immediately after the course. Statistical analysis revealed a significant increase in the overall level of entrepreneurial thinking and its key components, including initiative, creativity, risk-taking, result orientation, and persistence. The course featured innovative teaching methods such as project-based learning, case studies, and business games, and was offered as an elective module on an experimental educational platform. The findings are consistent with international research, highlighting the importance of integrating entrepreneurial thinking into teacher training to enhance professional preparedness. These findings can help shape modern educational programs in Kazakhstan and the countries of the Commonwealth of Independent States, in line with global trends and the challenges of the 21st century.